Effect of particle size of variolls energy and protein sources on hardness Rnd setting time of urea-molasses mineral lick blocks - SIHAG, ZILE S; CHAHAL, S M; PUNIA, B S (The Indian Journal of Animal Sciences, 2014)
Experiments were conducted to study the hardness and setting time of urea molasses mineral block (UMMB) formulated from 4 energy sources (deoiled rice bran, maize, barley, wheat bran), 3 protein sources (mustard-cake, groundnut-cake, sunflower-cake), 4 particle sizes (coarse, medium, fine, mixture) and 4 molasses levels (45, 50, 55, 60%), in a 4x3x4x4 factorial design. Hardness of blocks decreased (P